The Effect of Fan Blade Radiator Gas Turbin Generator Angle on Auxiliary Cooling Water System Performance - Erryawan Kusuma; Agus Sigit Pramono (IPTEK The Journal of Engineering, 2019)
Auxiliary Cooling Water System (ACWS) on Gas turbine Blok 1 No 3 Muara Karang has declined its reliability because of 4 fan radiators must be operated due to increasing ambient air temperature and increase inspection interval from 8000 to 32.000 EOH after Upgrade in turbine part. This study aims to optimize Radiator ACWS performance by increasing the cooling fan air mass flow by changing the fan blade angle so it can be operated with 3 fan on and 1 fan standby. This research began with taking data each measurement at 11°, 13°, 15°, 17°, and 19°. Then, it will simulated by software to know the influence of air mass flow addition due to the change of the blade fan angle to the radiator water outlet temperature and to know the input operating parameters when the temperature outlet radiator is 46°C. The results of this study is validation of experimental and numerical data calculations that have errors below 5%. The maximum angle of fan blade can be set until 19°. At 16.7° with operation 3 of 4 fan on, radiator temperature output is 46° and heat disposed is 627.2 kW where this value is the same value as the current condition.